1991
DOI: 10.1523/jneurosci.11-09-02795.1991
|View full text |Cite
|
Sign up to set email alerts
|

Mossy fiber synaptic reorganization induced by kindling: time course of development, progression, and permanence

Abstract: Recent studies have revealed that mossy fiber axons of granule cells in the dentate gyrus undergo reorganization of their terminal projections in both animal models of epilepsy and human epilepsy. This synaptic reorganization has been demonstrated by the Timm method, a histochemical technique that selectively labels synaptic terminals of mossy fibers because of their high zinc content. It has been generally presumed that the reorganization of the terminal projections of the mossy fiber pathway is a consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
273
2
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 490 publications
(296 citation statements)
references
References 43 publications
18
273
2
3
Order By: Relevance
“…Based on these data, it would appear that accumulation of 7S SNARE complexes does correlate with a stable, kindling-induced, epileptic state. Amygdalar and entorhinal kindling has been associated with hippocampal mossy fiber sprouting and dentate granule cell neuronal loss (Cavazos et al, 1991). (Osawa et al, 2001) have demonstrated that in the case of amygdalar stimulation, kindling develops without evidence of mossy fiber sprouting until after repeated kindled convulsions, following death of granule cells in the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data, it would appear that accumulation of 7S SNARE complexes does correlate with a stable, kindling-induced, epileptic state. Amygdalar and entorhinal kindling has been associated with hippocampal mossy fiber sprouting and dentate granule cell neuronal loss (Cavazos et al, 1991). (Osawa et al, 2001) have demonstrated that in the case of amygdalar stimulation, kindling develops without evidence of mossy fiber sprouting until after repeated kindled convulsions, following death of granule cells in the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…The kindling model of experimental epileptogenesis involves the generation of spontaneous seizures together with reorganization of mossy fiber synapses (McNamara, 1988;Sutula et al, 1988;Ben-Ari and Represa, 1990;Cavazos et al, 1991). It is interesting that together with synaptic reorganization of mossy fiber projections there appeared new [3H]kainate binding sites in the infrapyramidal cell layer of the CA3 subregion (Ben-Ari and Represa, 1990).…”
Section: Excitotoxicitymentioning
confidence: 99%
“…Once established, kindling results in a permanent state of seizure susceptibility, which may manifest as spontaneous epileptiform seizures (Pinel and Rovner, 1978). Kindling has recently been shown to induce a variety of permanent structural changes in the brain, including sprouting of the mossy fiber pathway that originates from hippocampal dentate gyrus (DG) granule cells (Sutula et al, 1988;Cavazos et al, 1991) and neuronal loss in the hippocampus (Cavazos et al, 1994).…”
Section: Introductionmentioning
confidence: 99%